Hungarian Monitoring, 22 February 1988 . [Magyar rádiófigyelő], 1988. február 22 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Gorbachev-Schultz meeting - New Cypriot president's speech - Border corrections along the Berlin Wall - 45th anniversary of the Warsaw Ghetto uprising Domestic Affairs: - Gromyko's visit - Károly Grósz in talks with Austrian finance minister Graf - Károly Grósz receives Hungarian writers in the Parliament - Defense Minister awarded decoration - The book trade Economy: - Director of Rába and deputy industry minister on the prospects for domestic car production - Transelektro's latest deals: Turkish power plant with Siemens, giant furnace for India Külpolitika: - Gorbacsov-Schultz találkozó - Az új ciprusi elnök beszéde - Határkiigazítások a berlini fal mentén - A varsói gettólázadás 45. évfordulója Belpolitika: - Gromiko látogatás - Grósz Károly Graf osztrák gazdasági miniszterrel tárgyal - Grósz Károly magyar írókat fogad a Parlamentben - A honvédelmi miniszter kitüntetése - Könyvkereskedelem Gazdaság: - A hazai autógyártás esélyeiről a Rába igazgatója és az ipari miniszterhelyettes - Törökországi erőmű a Siemens-szel, óriáskazán Indiának: a Transelektro legújabb üzletkötései